Intrasession and intersession reliability of countermovement jump testing in division-I volleyball athletes - Carroll, M. K.; Wagle, P. J.; Sole, J. C.; Stone, H. M. (The Journal of Strength and Conditioning Research, 2019)
The countermovement jump (CMJ) is a reliable and noninvasive test of lower-body neuromuscular performance. Many of the investigations used to establish the reliability of CMJ have been conducted in a controlled environment (i.e., laboratory setting). To better inform coaches, reliability of key CMJ variables should be examined in a practical environment. This study assessed intrasession and intersession reliability of CMJ variables in NCAA D-I volleyball athletes. Eleven female volleyball players (age = 19.8 ± 0.8 years, height = 1.75 ± 0.07 m, body mass = 71.6 ± 8.9 kg) performed twice weekly CMJ testing on force platforms across 14 weeks of training. Dependent variables were CMJ height (CMJH), reactive strength index modified (RSIMOD), relative peak power (rPP), and countermovement depth (CM depth). Intraclass correlation coefficients (ICCs), coefficient of variation (CV), and typical error (TE) were calculated, along with Pearson correlation coefficients. Intrasession reliability revealed excellent reliability values for CMJH (ICC = 0.94, CV = 2.9 ± 2.4%, TE = 1.25) and RSIMOD (ICC = 0.93, CV = 4.7 ± 4.9, TE = 0.03). Good reliability values were observed for rPP (ICC = 0.79, CV = 6.1 ± 10.9%, TE = 4.48), with only moderate reliability for CM depth (ICC = 0.61, CV = 7.1 ± 10.9%, TE = 16.9). Intersession reliability indicated excellent reliability for CMJH (ICC = 0.92, CV = 3.2 ± 2.8%, TE = 1.4) and RSIMOD (ICC = 0.92, CV = 5.4 ± 4.3%, TE = 0.03). However, poor reliability was observed for rPP (ICC = 0.41, CV = 10.4 ± 15.4%, TE = 7.95) and CM depth (ICC = 0.39, CV = 7.7 ± 10.8%, TE = 6.42). These results suggest that in the context of weekly athlete monitoring, measures such as CMJH and RSIMOD exhibit the greatest reliability. Conversely, measures such as CM depth and rPP exhibit high levels of variability. Practitioners seeking to track jump performance over time should be cognizant of CM depth variability and its potential impact on CMJ variables.